Homo an Liber? Zur Ethik des Scherzens in Cicero, De Off. 1, 103 f. - Dunsch, Boris (Hyperboreus, 2013)
In his treatment of temperantia (De off. 1, 93–151), Cicero discusses the self-evident natural principle of decorum, closely linked with that of honestum. Cicero illustrates it by an analogy from drama, where a person’s utterance should suit his/her character. Thus decorum requires us to control, among other things, our wit and jest. There are two kinds of them, one in accordance with decorum, the other not. The vulgate reading of a central statement about iocus is: Alter est, si tempore ﬁt, ut si remisso animo, <vel severissimo> homine dignus, alter ne libero quidem, si rerum turpitudo adhibetur aut verborum obscenitas. In the context of Cicero’s argument, it makes better sense to abstain from the insertion <vel severissimo> and read: et<iam>si remisso animo, homine dignus, where homo refers to all human beings (including slaves) and liber to all free human beings. A biographical cause for Cicero’s discussion can be found in an attack waged on him by Antonius, accusing him of undue joking while he stayed at Pompey’s camp (Phil. 2, 39).